The Ordospora colligata Genome: Evolution of Extreme Reduction in Microsporidia and Host-To-Parasite Horizontal Gene Transfer - Jean-François Pombert; Karen Luisa Haag; Shadi Beidas; Dieter Ebert; Patrick J. Keeling (mBio, 2015)
ABSTRACT  Microsporidia are a group of obligate intracellular parasites that are best known for their unique infection mechanism and their unparalleled levels of genomic reduction and compaction. We sequenced the genome of Ordospora colligata, a gut parasite of the microcrustacean Daphnia sp. and the closest known relative to the microsporidia characterized by the most extreme genomic reduction, the model genus Encephalitozoon. We found that the O. colligata genome is as compact as those of Encephalitozoon spp., featuring few introns and a similar complement of about 2,000 genes, altogether showing that the extreme reduction took place before the origin of Encephalitozoon spp. and their adaptation to vertebrate hosts. We also found that the O. colligata genome has acquired by horizontal transfer from its animal host a septin that is structurally analogous to septin 7, a protein that plays a major role in the endocytosis-based invasion mechanism of the fungal pathogen Candida albicans. Microsporidian invasion is most often characterized by injection through a projectile tube, but microsporidia are also known to invade cells by inducing endocytosis. Given the function of septins in other systems, we hypothesize that the acquired septin could help O. colligata induce its uptake by mimicking host receptors. IMPORTANCE The smallest known eukaryotic genomes are found in members of the Encephalitozoon genus of microsporidian parasites. Their extreme compaction, however, is not characteristic of the group, whose genomes can differ by an order of magnitude. The processes and evolutionary forces that led the Encephalitozoon genomes to shed so much of their ancestral baggage are unclear. We sequenced the genome of Ordospora colligata, a parasite of the water flea Daphnia sp. and the closest known relative of Encephalitozoon species, and show that this extreme reduction predated the split between the two lineages. We also found that O. colligata has acquired a septin gene by host-to-parasite horizontal transfer and predicted that the encoded protein folds like a septin 7, which plays a major role in endocytosis. We hypothesize that this acquisition could help O. colligata parasitize its hosts by facilitating endocytic infection, a mechanism that occurs in microsporidia but that is not yet well understood.